The Relationship Between Coffee Consumption Behavior, Poor Sleep Patterns, and Smoking Habits with the Incidence of Hypertension in Firefighters - Eva Ellya Sibagariang; Irma Lusty Margaretha Tumanggor; Mafe Robbi Simanjuntak (Universitas Pahlawan Tuanku Tambusai, 2026)
Hypertension is a non-communicable disease with high prevalence that constitutes a global health burden. Firefighters are a high-risk group due to heavy workloads, rotating shift systems, and unhealthy lifestyle behaviors. This study aimed to analyze the relationship between coffee consumption, poor sleep quality, and smoking habits with hypertension among firefighters at the Medan City Fire and Rescue Department. A quantitative cross-sectional design was used with 60 firefighters selected by total sampling. Data were collected using a coffee consumption questionnaire, Pittsburgh Sleep Quality Index (PSQI), Fagerström Test for Nicotine Dependence (FTND), and sphygmomanometer blood pressure measurements. Bivariate analysis used the Chi-Square test (α=0.05). Results showed 35.0% had hypertension and 40.0% were prehypertensive. No significant relationship was found between coffee consumption (p=0.881), poor sleep quality (p=0.257), and smoking habits (p=0.200) with hypertension. However, the prevalence of above-normal blood pressure reached 75%, far exceeding the national rate of 34.11%, indicating an urgent need for routine occupational health screening and health promotion programs.